Thar Sheetal fetches premium price - Choudhary, B R; Saroj, P L; Haldhar, S M; Maheshwari, S K; Singh, Dhurendra (Indian Horticulture, 2019)
Thar Sheetal, a high temperature tolerant variety of longmelon with moderate yield potential (130-140 q/ha), has been released by Central Institute for Arid Horticulture, Bikaner. It is recommended for hot arid region which set fruits at high temperature (up to 42Â°C) in summer. It is best adapted to low tunnel cultivation for early production, fetching premium prices.